2023
DOI: 10.1021/acs.energyfuels.2c03120
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Deactivation Behavior of MeMo/La2O3-Al2O3- and MeMo/Nb2O5 Supported Catalysts (Me = Pt, Ni, and Co) in Tri-Reforming of Methane

Abstract: The deactivation behaviors of MeMo/La2O3-Al2O3- and MeMo/Nb2O5 supported catalysts were investigated in the tri-reforming of methane (TRM). Characterizations by XRD, SEM-EDS, HRTEM, XPS, FTIR, and Raman spectroscopies were performed, after testing the catalysts in distinct TRM reaction conditions. The effects the transition metal components had on the causes of the deactivations of the solids were evaluated. The reaction conditions favored PtO x species residing in close contact with Mo sites to form a PtMo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…[185] 650-1100 [44] 3-25 [44] 0.9-1. TCD 58 [187,191] 500-1000 [162,163] 1 [162] 2 USD/Kg [8] 2.55-5 USD/Kg [12] 3.53-3.82 USD/kg [192] 1.72 USD/kg * Data available in literature refer to non-catalytic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[185] 650-1100 [44] 3-25 [44] 0.9-1. TCD 58 [187,191] 500-1000 [162,163] 1 [162] 2 USD/Kg [8] 2.55-5 USD/Kg [12] 3.53-3.82 USD/kg [192] 1.72 USD/kg * Data available in literature refer to non-catalytic process.…”
Section: Discussionmentioning
confidence: 99%
“…Kozonoe et al [162] compared carbon nanotubes and silica support for Ni catalysts and found that while both supports showed stable activity, carbon nanotubes offered better methane and carbon dioxide conversions, and also greater selectivity for hydrogen formation at 750 • C, mainly attributed to lower carbon dioxide activation by silica due to the acidic nature of the support. The deactivation behavior of bimetallic molybdenum catalysts supported on lanthana-alumina and on niobia determined that only NiMo catalysts are active on a lanthana-alumina support, while PtMo is active on a niobia support [163]. On a lanthanaalumina support, the Pt bimetallic catalyst rapidly deactivated due to sintering, while the CoMo catalyst deactivated due to oxidation of the cobalt species both on the lanthanaalumina and the niobia support.…”
Section: Autothermal Dual/tri-reformingmentioning
confidence: 99%